Literature Study on The Effectiveness of Gagne and Briggs Model in Learning - Muh. Asri Ilham; Qothrunnada Qothrunnada; Yunita Eka Putri; Satutik Rahayu (CATHA SAINTIFICA, 2025)
The Gagné and Briggs learning model is one of the systematic approaches used in instructional design. This literature study aims to analyze the effectiveness of the Gagné and Briggs model in improving learning outcomes based on a review of 50 research journals. The method used is a descriptive analysis of various studies that have been conducted in various educational contexts, ranging from primary to tertiary education, as well as in various subjects. The study results show that the model is effective in improving students' concept understanding, critical thinking skills and long-term retention. In addition, this model also supports a more structured and systematic learning process, making it easier for educators to develop teaching strategies. However, there are some challenges in implementing this model, such as the need for careful planning and adjustments to the characteristics of students. Thus, the Gagné and Briggs model remains relevant and can be applied effectively in various educational settings with some necessary adjustments.